A REVIEW OF THE IMPORTANCE, DETECTION AND CONTROLLING OF HEAVY METAL IN MILK AND DAIRY PRODUCTS - Mahmoudi, Razzagh; Kazeminia, Masoud; Kaboudari, Ata; Pir-Mahalleh, SeyedehFaezehRahimi; Pakbin, Babak (Malaysian Journal of Science, 2017)
Milk and dairy products can be contaminated in different ways. One of the most important and most challenging contaminations is due to heavy metals. In present research key words, including Milk, Dairy products, Heavy metal, Iran in the database pub med, Science Direct, Elsevier, SID, MagIran, Civilica, the World Health Organization and Agriculture Organization of the United Nations were searched. All articles indexed in domestic and international journals related to the topic were collected over the past several years. Heavy metal contamination in milk and dairy products play an important role in public health, as it can be the reason to the prevalence of diverse illnesses and lesions. There are various ways to measure the amount of contamination in milk and dairy products. One of the best and most efficient methods is atomic absorption. Moreover, collecting samples, storing and preparing them with different materials and solutions are also an important method. Heavy metals can enter the food chain in many ways. Sewage, factory waste, garbage, dust and etc are the common ways for heavy metals to enter the food. Cow’s body acts like a biological filter about heavy metals, especially Cadmium and the absorbed Lead and Cadmium move to its bones and start to accumulate. Due to extensive consumption of milk and dairy products, it is critical to lessen contamination. Water and foods with both animal and plant resources must be monitored and examined before use. Materials used for food packaging must be harmless for human health so the present elements used in the containers must be reconsidered. Key words: Milk, Dairy products, Heavy metal, Iran